Evaluating the long-term impact of adaptive reuse on heritage spaces: a case study of Aslam square in Cairo, Egypt - Yomna Amr Lotfi; Toka Fahmy Aly (Built Heritage)
Abstract Reusing heritage spaces as vibrant public areas can significantly enhance the quality of life and public spaces within a community. However, there is a notable gap in knowledge regarding evaluations of the success or failure of these upgrading and reuse initiatives. The literature suggests that evaluations should be conducted with comparative analyses of physical characteristics before and after the implementation of such programmes. This study proposes a post-adaptive reuse evaluation method for assessing the quality of heritage spaces and community development. The research employs methodological triangulation by incorporating sociospatial analysis with three methods: 1) deductive reasoning to assess the quality of heritage spaces; 2) in-depth interviews with users of these spaces; and 3) sensitivity to context observations. These methods were applied across three different timeframes: before the upgrade, three years after the upgrade, and ten years after the upgrade. This study therefore provides a comprehensive and longitudinal analysis. This study assesses the adaptive reuse of Aslam Square in the Darb Al Ahmar district of Cairo, Egypt. The findings demonstrate that the post-adaptive reuse evaluation method is appropriate, and its use is recommended as a cause-and-effect indicator to promote heritage spaces and local community development.